Back Cover: Hierarchical Pt/NiO Hollow Microspheres with Enhanced Catalytic Performance (ChemNanoMat 1/2015). Issue 1 (May 2015) - Qi, Lifang; Cheng, Bei; Ho, Wingkei; Liu, Gang; Yu, Jiaguo
Abstract : Heterogeneous Catalysis . In their Full Paper on10.1002/cnma.201400013 ((page 58, )) which is featured on the Back Cover, Wingkei Ho, Jiaguo Yu and co‐workers show that hierarchical macro‐mesoporous Pt/NiO hollow microspheres can be used for catalytic decomposition of formaldehyde (a major indoor air pollutant) in air at room temperature. The 400 °C‐calcined hollow spheres exhibit the highest catalytic activity due to the presence of bimodal macro‐mesoporous structures, which not only provide large specific surface areas, leading to high HCHO adsorption capacity and good Pt dispersion, but also enable fast diffusion and gas molecule transport and ensure the accessibility of the active sites on Pt nanoparticles.